Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019 IEEE International Conference on Electrical, Computer and Communication Technologies (ICECCT) 2019
DOI: 10.1109/icecct.2019.8869364
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia Detection Using CNN based Feature Extraction

Abstract: Pneumonia is a life-threatening infectious disease affecting one or both lungs in humans commonly caused by bacteria called Streptococcus pneumoniae. One in three deaths in India is caused due to pneumonia as reported by World Health Organization (WHO). Chest X-Rays which are used to diagnose pneumonia need expert radiotherapists for evaluation. Thus, developing an automatic system for detecting pneumonia would be beneficial for treating the disease without any delay particularly in remote areas. Due to the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
87
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 307 publications
(124 citation statements)
references
References 18 publications
1
87
0
10
Order By: Relevance
“…Li et al (2018) used Den-seNet-121 and DenseNet-RNN were two deep learning models utilized to analyze the infections in ChestX-Ray14, where DenseNet-121 getting a sum of 74.5% and DenseNet-RNN was 75.1% to recognizing Pneumonia. Rajpurkar et al (2017) were introduced by taking 121 layers to identify one of the 14 infections at 76.8% of accuracy of the pneumonic class from the others; likewise this model gives a heatmap for possible localization that depends on the forecast done by the convolutional neural network, and more study can be found by applying machine learning and deep learning algorithm to analyze the X-ray and CT images (Basu et al 2020;Pavithra et al 2015;Ozkaya et al 2020;Santos and Melin 2020;Tolga et al 2020;Ramírez et al 2019;Miramontes et al 2018;Melin et al 2018;Kermany, et al 2018b, a;Ayan, and Ü nver, 2019;Varshni et al 2019;Wang et al 2017;Togaçar et al 2019;Jaiswal, et al 2019;Sirazitdinov, et al 2019;Behzadi-khormouji et al 2020;Stephen et al 2019;Xu et al 2020;Shan et al 2020).…”
mentioning
confidence: 99%
“…Li et al (2018) used Den-seNet-121 and DenseNet-RNN were two deep learning models utilized to analyze the infections in ChestX-Ray14, where DenseNet-121 getting a sum of 74.5% and DenseNet-RNN was 75.1% to recognizing Pneumonia. Rajpurkar et al (2017) were introduced by taking 121 layers to identify one of the 14 infections at 76.8% of accuracy of the pneumonic class from the others; likewise this model gives a heatmap for possible localization that depends on the forecast done by the convolutional neural network, and more study can be found by applying machine learning and deep learning algorithm to analyze the X-ray and CT images (Basu et al 2020;Pavithra et al 2015;Ozkaya et al 2020;Santos and Melin 2020;Tolga et al 2020;Ramírez et al 2019;Miramontes et al 2018;Melin et al 2018;Kermany, et al 2018b, a;Ayan, and Ü nver, 2019;Varshni et al 2019;Wang et al 2017;Togaçar et al 2019;Jaiswal, et al 2019;Sirazitdinov, et al 2019;Behzadi-khormouji et al 2020;Stephen et al 2019;Xu et al 2020;Shan et al 2020).…”
mentioning
confidence: 99%
“…X-ception network is more felicitous for classifying X-ray images than VGG-16 network. Varshni et al [46] proposed pre-trained ConvNet models (VGG-16, Xception, Res50, Dense-121, and Dense-169) as feature-extractors followed by different classifiers Symmetry 2020, 12, 651 5 of 19 (SVM, Random Forest, k-nearest neighbors, Naïve Bayes) for the detection of normal and abnormal pneumonia X-rays images. The prosaists used ChestX-ray14 introduced by Wang et al [47].…”
Section: Related Workmentioning
confidence: 99%
“…The usage of deep learning models in medical image processing and analysis is a challenging topic in the AI field [10,20]. In [21], the authors propose a CNN model for pneumonia detection. The authors of the study [22] propose a vessel extraction from the fundus images.…”
Section: Introductionmentioning
confidence: 99%